Ethics briefings - Chrispin, E. (Journal of medical ethics, 2009)
LuxembourgIn December 2008, the issue of euthanasia provoked constitutional change in Luxembourg, when, contrary to the monarch’s wishes, Parliament endorsed a law permitting euthanasia for terminally ill patients. Parliament had voted by a small majority (30 to 26) in February 2008 to legalise euthanasia1 and the law was expected to come into force last summer but the second parliamentary reading was postponed until December. Luxembourg is a predominantly Catholic country and Pope Benedict XVI condemned the legislation shortly before the Parliament endorsed it. A constitutional crisis arose when Grand Duke Henri refused to sign the law as no legislation could come into force without his consent. He agreed, however, to a constitutional amendment removing his power of veto. Some saw this as a parallel with the decision taken by his uncle, King Baudoin of Belgium, who in 1990 abdicated for one day in order to avoid signing the Belgian abortion law. This change in the Luxembourg constitution permanently limits the monarch to announcing Parliament’s decisions rather than endorsing them.2UKAlso in December 2008, The Sunday Times commissioned a survey of public opinion.3 The survey of over 2000 people found that most would consider euthanasia for themselves and thought that relatives who take terminally ill people to foreign clinics for assisted suicide should not be prosecuted. The poll followed a Sky TV broadcast of the assisted suicide in Switzerland of Craig Ewert: 61% of poll respondents said it was right to screen his death. More than two thirds (69%) said that the law should be changed to give relatives immunity from prosecution if they accompany a person seeking assisted dying abroad. A majority (61%) said they would consider assisted suicide for themselves against 15% who would not. …